Sediment properties, geochemical proxies, clay mineral composition and diatom assemblage of gravity cores obtained on the Drygalski Basin in the Ross Sea since Last Glacial Maximum - Sangbeom Ha; Jae Il Lee; Young-Suk Bak; Kyu-Cheul Yoo; Boo-Keun Khim (PANGAEA, 2024)
For the reconstruction of paleoenvironment and retreat of grounding line and calving line, magnetic susceptibility, granulometry, biogenic opal, total organic carbon, d13C, total nitrogen, total organic carbon-total nitrogen ratio, CaCO3, clay mineral composition, diatom assemblage were analyzed. During the DG12 Expedition in 2012 using Korean I/B ARAON, gravity cores(DG12-GC01, GC02, GC04, and GC05) were obtained on the northern Drygalski Basin in the Ross Sea since Last Glacial Maximum.